2019
DOI: 10.1039/c9ra03902c
|View full text |Cite
|
Sign up to set email alerts
|

One pot conversion of glucose to ethyl levulinate over a porous hydrothermal acid catalyst in green solvents

Abstract: One-pot conversion of glucose to ethyl levulinate over an acid-functionalised hydrothermal carbon gives high initial yields up to 37 mol% (comparable to H2SO4) with catalyst performance strongly influenced by green solvent choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…After 2 h of reaction at 200 °C, the EL yield was 23.5 mol%. HTC‐400‐S had strong catalytic activity, and an EL yield of 37 mol% was obtained from a reaction performed at 200 °C for 6 h 80 . In our work, the EL yield obtained using SO 4 2− /ZrO 2 @Al 2 O 3 ‐3M at 200 °C after 5 h was 37.5 mol%.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…After 2 h of reaction at 200 °C, the EL yield was 23.5 mol%. HTC‐400‐S had strong catalytic activity, and an EL yield of 37 mol% was obtained from a reaction performed at 200 °C for 6 h 80 . In our work, the EL yield obtained using SO 4 2− /ZrO 2 @Al 2 O 3 ‐3M at 200 °C after 5 h was 37.5 mol%.…”
Section: Resultsmentioning
confidence: 54%
“…The catalytic performance of SO 4 2− /ZrO 2 @Al 2 O 3 is compared to those reported for hyper‐crosslinked polymer‐based carbonaceous materials, a hybrid zirconia zeolite, H‐ZSM‐5‐supported phosphotungstic acid (HPW/H‐ZSM‐5), SO 4 2− /ZrO 2 grafted SBA‐15 type double acid solid acid catalyst (SZ/SBA‐15), SO 4 2− /ZrO 2 –Al 2 O 3 and sulfonated hydrothermal carbon (HTC‐400‐S) in Table 2 16, 17, 21, 75, 79, 80 . The hyper‐crosslinked polymer‐based carbonaceous materials and hybrid zirconia zeolite were weak catalysts, and the EL yields obtained with the catalysts were 25 mol% (170 °C, 8 h) and 21 mol% (230 °C, 6 h), respectively 16, 17 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternative use of chemical heterogeneous catalysts was reported, such as the commercial heteropolyacids, sulfated metal oxides, zeolite molecular sieves and hydrotalcite-like compounds [69], whose also present the disadvantage of high cost. Recently, Bosilj et al [98] reported the use of a cheaper biomass-derived catalyst in the conversion of glucose into ethyl levulinate (EL). In this study, an acid-functionalized hydrothermal catalyst derived from glucose was produced by hydrothermal carbonization of glucose that was first treated with sodium borate (borax) to generate carbon nanoparticle size and, then, it was sulfonated with H2SO4.…”
Section: Alkyl Levulinatesmentioning
confidence: 99%
“…HTC of saccharides is known to produce microspherical hydrochar. 4 Numerous saccharides, such as glucose, 5,6 sucrose, 7 cyclodextrin, 8 fructose, 9 xylose, 10 cellulose, 11 agarose 12 and starch, 13 have been shown to result in microspheres (MS) with mostly Gaussian size distributions. The underlying chemical mechanisms during HTC of saccharides include dehydration, condensation, polymerization, and aromatization.…”
Section: Introductionmentioning
confidence: 99%